Information on the conference ASADE-2007 (Algebra and Discrete Mathematics, 2007)
The international conference “Algebraic systems and their applications in differential equations and other domains of mathematics” took place in Chisinau (Republic of Moldova) from 21-st to 23-rd of August 2007. It was organized by the Institute of Mathematics and Computer Science of Academy of Sciences of Moldova in collaboration with Mathematical Society of Moldova and some state universities of the country.